Effect of integrated nutrient management with mycorrhizal bio-fertilizer on physical and bio-chemical properties of soil in planted and ratoon crop of sugarcane - KUMAR, MANJUL; KUMAR, NEERAJ (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted at Agronomy research farm of Acharya Narendra Deva University of Agriculture & Technology, Kumarganj, Ayodhya, Uttar Pradesh, India. to study the effect of integrated nutrient management on soil properties and yield of sugarcane. The experiment was conducted in randomized block design with three replications and twelve treatments.The treatments consisted of three rates of MBF mycorrhizal bio-fertilizer @ 10, 15 and 20 kg/ha at the time of planting and same amount MBF after three months of planting in combination with three levels of RDF (100, 75 and 50 % RDF). These treatments were evaluated in three replications with Sugarcane (var. COS- 88230) during 2013-15 on plant–ratoon in sequence. Microbial population (bacteria, fungi and actinomycetes) and higher availability of nutrients in soil were recorded with the treatment T3 MBF @ 20 kg/ha at the time planting and three months after planting) + 100% RDF which was showed impressive improvement in microbial population and availability of nutrients ahead sustainable manner with nature through use of MBFMBF in combination with inorganic fertilizers